Multitier cropping systems for resource conservation and higher productivity in eastern ghat highland zone of Odisha - Jakhar, Praveen; Dass, Anchal; Sudhishri, Susama; Naik, B.S.; Panda, R.K. (Annals of Agricultural Research, 2014)
An experiment consisting of five multitier cropping systems comprising square planting (4m x 4m) of two fruit trees (papaya and drumstick), Gliricidia or No-Gliricidia planting on plot boundary with ginger as intercrop and a control (farmers’ practice of broadcast sown fingermillet) was carried out for four years (2007-2010) on 2% sloping land having sandy clayey red lateritic soil in Eastern Ghat Highland zone of Odisha. Planting papaya and drumstick along with ginger arrested the runoff by 6.05 and 5.24% compared to control. Gliricidia planted on boundary of papaya + ginger and drumstick + ginger plots decreased soil loss by 8.64 and 7.88 t/ha, respectively, over control. These multitier cropping systems reduced nutrient losses (N, P and K) by about 50%. Gliricidia improved ginger yield by 11.5% under papaya + Gliricidia and 8.6% under drumstick + Gliricidia system over papaya and drumstick sole treatments. Maximum net returns ( 2.29 lakhs ha-1) were obtained from ginger + papaya + Gliricidia with benefit: cost ratio of 1.67. Farmers’ practice (broadcasting of finger millet) was not found economical as it gave benefit: cost ratio below 1 and allowed higher runoff, soil and nutrient losses.